Determination of Combustion Kinetic Parameters of Microalgal Wastes - Kocer, Anil T.; Ozcimen, Didem (Mehmet Sinan Bilgili, 2020)
Microalgae, new generation feedstocks, can be used in many different areas and have a high waste potential with their utilization processes in various industries. So, management and evaluation of these algal wastes are important. Although the formation of microalgal wastes has been minimized with the biorefinery approach recently, the formation of these wastes cannot be completely prevented. In this context, the evaluation of these wastes is an issue investigated by researchers. In this study, it is aimed to investigate the combustion characteristics of waste of oil-extracted Chlorella minutissima. So, the combustion characteristics of this algal waste were investigated by the thermogravimetric method and kinetic parameters were determined by using Kissinger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO) methods. According to the results, it was seen that the combustion of microalgal waste took place in three stages. In the first stage, moisture was removed from the biomass between approximate temperatures of 25 and 175 degrees C. In the second stage, organic volatile substances were decomposed between temperature of 175 and 535 degrees C. In the third stage, solid carbonaceous structures burned between temperatures of 535 and 700 degrees C. As a result of the calculations made to determine the combustion kinetics, the combustion activation energies of algal waste were found to be 194.62 kJ/mol and 195.97 kJ/mol for KAS and FWO methods, respectively. It can be concluded that algal waste obtained after extraction process can be used directly as a fuel or by mixing it with other solid fuels in combustion processes.
Keywords: Combustion kinetic; Microalgae; Algal waste; Thermogravimetry; THERMOGRAVIMETRIC ANALYSIS; Engineering; Environmental Sciences & Ecology